Eddies of the Cape Verde Archipelago - Cardoso, Cláudio Roberto Fernandes de Góis (2017)
The characterisation of the mesoscale eddy field within and around the Cape Verde Archipelago is presented. Special attention is regarded towards the far-field (incoming) and the near-field (island-induced) eddies, along with the mechanisms and processes influencing their generation and evolution. Consequent implications in the local biological primary production (Island Mass Effect, or IME) are also assessed. This is achieved by combining remote-sensing satellite observations for wind, ocean surface currents, ocean surface topography, clorophyll a surface concentrations and sea surface temperature. Results show that the interaction between far-field eddies and the archipelago is a recurrent phenomenon, which results in eddy transformation, eddy termination, eddy splitting, and eddy deflection. Local island-induced disturbances are also significant, mainly by atmospheric effects. Such processes result in the generation and confinement of mesoscale eddies, more often observed in the leeward group. However, the distinction between island-induced and far-field processes is hindered by the complex interaction between both fields. Thus, it is strongly suggested that many of the near-field eddies are a direct product or a by-product of such interaction. This is even more obvious in the assessment of the IME. Far-field eddies are often associated with enhanced Clha concentrations. However, nutrient-injection by island-induced cyclonic eddies also gives rise to phytoplankton blooms. As the remote and island-driven biological enhancement are remarkably intertwined, such observations challenge the idea that local biological productivity in deep oceanic islands are exclusively driven by island-induced mechanisms.